Induction of human hemogenesis in adult fibroblasts by defined factors and hematopoietic coculture. Issue 23 (12th October 2019) - Daniel, Michael G.; Sachs, David; Bernitz, Jeffrey M.; Fstkchyan, Yesai; Rapp, Katrina; Satija, Namita; Law, Kenneth; Patel, Foram; Gomes, Andreia M.; Kim, Huen‐Suk; Pereira, Carlos‐Filipe; Chen, Benjamin; et al.
Abstract : Transcription factor (TF)‐based reprogramming of somatic tissues holds great promise for regenerative medicine. Previously, we demonstrated that the TFs GATA2, GFI1B, and FOS convert mouse and human fibroblasts to hemogenic endothelial‐like precursors that generate hematopoietic stem progenitor (HSPC)‐like cells over time. This conversion is lacking in robustness both in yield and biological function. Herein, we show that inclusion of GFI1 to the reprogramming cocktail significantly expands the HSPC‐like population. AFT024 coculture imparts functional potential to these cells and allows quantification of stem cell frequency. Altogether, we demonstrate an improved human hemogenic induction protocol that could provide a valuable human in vitro model of hematopoiesis for disease modeling and a platform for cell‐based therapeutics. Database: Gene expression data are available in the Gene Expression Omnibus (GEO) database under the accession number GSE130361 .